The Effects of Chest Wall Loading on Perceptions of Fatigue, Exercise Performance, Pulmonary Function, and Muscle Perfusion - Gaia Giuriato; Anders Gundersen; Sarina Verma; Ethan Pelletier; Brock Bakewell; Stephen J. Ives (MDPI AG, 2020)
Background: Load carriage (LC), which directly affects the chest wall and locomotor muscles, has been suggested to alter the ventilatory and circulatory responses to exercise, leading to increased respiratory muscle work and fatigue. However, studies exploring the impact of LC on locomotion increased internal work, complicating their interpretation. To overcome this issue, we sought to determine the effect of chest wall loading with restriction (CWL + R) on cycling performance, cardiopulmonary responses, microvascular responsiveness, and perceptions of fatigue. Methods: In a randomized crossover design, 23 young healthy males (22 ± 4 years) completed a 5 km cycling time trial (TT) in loaded (CWL + R; tightened vest with 10% body weight) and unloaded conditions. After baseline pulmonary function testing (PFT; forced expiratory volume in 1 s, FEV1; forced vital capacity, FVC), cardiopulmonary indices (HR, heart rate; O2 uptake, VO2; ventilation, VE; tidal volume, VT; and breathing frequency, Bf), rating of perceived exertion (RPE), lactate (BLa), and microvascular responses (oxy-, deoxy-, total hemoglobin; and tissue saturation; StO2) of the vastus lateralis using near infrared spectroscopy were collected during the TT; and PFT was repeated post-exercise. Results: Pre-exercise, CWL + R reduced (p < 0.05) FVC (5.6 ± 0.8 versus 5.5 ± 0.7 L), FEV1 (4.8 ± 0.7 versus 4.7 ± 0.6 L), and FEV1/FVC (0.9 ± 0.1 versus 0.8 ± 0.1). CWL + R modified power output (PO) over time (interaction, p = 0.02), although the 5 km time (461 ± 24 versus 470 ± 27 s), VT (3.0 ± 0.3 versus 2.8 ± 0.8 L), Bf, VE, HR, VO2, microvascular and perceptual (visual analog scale, or VAS, and RPE) responses were unchanged (p > 0.05). CWL + R increased (p < 0.05) the average BLa (7.6 ± 2.6 versus 8.6 ± 3 mmol/L). Conclusions: Modest CWL + R negatively affects pre-exercise pulmonary function, modifies cycling power output over time, and increases lactate production during a 5 km cycling trial, although the cardiorespiratory, microvascular, and perceptual responses were unaffected.